P458 Safety and Potential Efficacy of Escalating Dose of Ustekinumab in Pediatric Crohn's disease (the SPEED-UP study) - A multi-center study from the paediatric IBD Porto group of ESPGHAN. (21st January 2022) - Yerushalmy-Feler, A; Pujol-Muncunill, G; Martin-de-Carpi, J; Kolho, K L; Levine, A; Olbjørn, C; Granot, M; Bramuzzo, M; Jonsson Rolandsdotter, H; Mouratidou, N; Hradsky, O; Scarallo, L; et al.
Abstract: Background: Ustekinumab (UST) is an effective therapy for induction and maintenance of remission in Crohn's disease (CD). Intensification of UST maintenance dosage has shown effectiveness in some adult patients, but no similar data are available in children. The aim of the study was to evaluate the effectiveness and safety of dose escalation of UST in paediatric CD. Methods: This was a retrospective multicenter study from 25 centers affiliated to the IBD Interest and Porto groups of ESPGHAN. We included children with CD who initiated UST at a standard dosing and subsequently underwent dose escalation to intervals shorter than 8 weeks, or re-induction due to active disease. Demographic, clinical, laboratory, endoscopic and imaging data were collected at escalation and during a 12 months follow-up. Clinical remission was defined as weighted Paediatric Crohn's Disease Activity Index (wPCDAI)<12.5 and clinical response as a decline in >17.5 points. Adverse events were explicitly recorded. Results: Sixty-nine children, with a median age of 15.8 (IQR 13.8–16.9) years and disease duration of 4.3 (2.9–6.3) years were included. Sixty-eight (98.6%) and 59 (86.8%) children were biologic and immunomodulators experienced, respectively. UST dose was escalated after a median of 6 (3.6–12) months of therapy. Clinical response and remission were observed in 46 (67%) and 29 (42%) children at 3 months, respectively. The strongest predictor of clinical remission was lower wPCDAI at escalation (p=0.001). The median serum levels of C-reactive protein decreased from 14 (3–28.03) to 5 (1.1–20.5) mg/L at 3 months (p=0.012), and fecal calprotectin from 1110 (499–2300) to 248 (118–1159) mcg/g at 12 months (p=0.05). Endoscopic and transmural healing were achieved in 3/19 (16%) and 2/15 (13%) patients, respectively, of those with available tests. Overall, 13 patients (19%) discontinued therapy due to active disease, at a median of 3 (3–4.5) months. No serious adverse events were reported. Conclusion: Two-thirds of children with active CD achieved response following dose escalation of UST.